2015
DOI: 10.1371/journal.pone.0139962
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Circulating Lymphocyte Subpopulations with Type 2 Diabetes: Cross-Sectional Results from the Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: ObjectiveDistinct lymphocyte subpopulations have been implicated in the regulation of glucose homeostasis and obesity-associated inflammation in mouse models of insulin resistance. Information on the relationships of lymphocyte subpopulations with type 2 diabetes remain limited in human population-based cohort studies.MethodsCirculating levels of innate (γδ T, natural killer (NK)) and adaptive immune (CD4+ naive, CD4+ memory, Th1, and Th2) lymphocyte subpopulations were measured by flow cytometry in the periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 52 publications
5
32
0
2
Order By: Relevance
“…The 13 included studies were published in between 2008 and 2019. Additionally, the geographic distribution of the included studies comprised of Europe ( n = 6) [ 14 – 17 , 21 , 27 ], Northern America ( n = 2) [ 20 , 23 ], Africa ( n = 1) [ 24 ], and Asia ( n = 4) [ 19 , 25 , 27 , 28 ]. Two studies were longitudinal prospective studies [ 22 ] and the remaining 9 studies were cross-sectional studies [ 15 – 17 , 21 , 23 , 26 , 27 , 29 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 13 included studies were published in between 2008 and 2019. Additionally, the geographic distribution of the included studies comprised of Europe ( n = 6) [ 14 – 17 , 21 , 27 ], Northern America ( n = 2) [ 20 , 23 ], Africa ( n = 1) [ 24 ], and Asia ( n = 4) [ 19 , 25 , 27 , 28 ]. Two studies were longitudinal prospective studies [ 22 ] and the remaining 9 studies were cross-sectional studies [ 15 – 17 , 21 , 23 , 26 , 27 , 29 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 13 studies fulfilled the study selection criteria and were included in the qualitative analysis [14-22, 24, 25, 27, 28, 35]. While only six studies were included in the meta-analysis [14,15,[19][20][21]35].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In non-insulin-dependent diabetes mellitus (NIDDM) subjects, a report that analyzed the T-cell subsets after phytohemagglutinin stimulation by flow cytometry indicated no statistically significant differences between the subsets of CD4 + and CD8 + T-cells from peripheral blood of patients with diabetes and the healthy controls (21). Olson et al investigated whether high degree of chronic adaptive immune activation, characterized by higher memory and lower naive CD4 + T-cells, was positively associated with type 2 DM (22). It was revealed that the associations of higher memory and lower naive CD4 + Tcells with type 2 DM was consistent with the role of chronic adaptive immune activation.…”
Section: Discussionmentioning
confidence: 99%